The Effect of Punching Bag Drills with Intervals on Anaerobic Endurance in Boxers - Prabowo, Trisnar Adi; Wangi, Sekar Pudak (Journal Sport Science Indonesia, 2025)
The purpose of this study was to analyze the use of interval training in Punching Bag drills on anaerobic endurance in boxers. This type of research is quasi-experimental, with pretest-posttest. The experimental group (EG) is a group with Punching Bag drills training with interval training, while the control group (CG) is a group with Punching Bag drills training but does not use intervals or free training. Data collection used a 300-meter sprint. The sample consisted of 7 EG boxers and 7 CG boxers, with characteristics of age 18 – 24 years, height 160 – 174 centimeters, weight 52 – 66 kilograms, training experience 3.2±2.7 years. The training program was conducted for 6 weeks, 3 meetings per week. EG and CG were also given the same opportunity in the form of 15 rounds x 3 minutes, 1 minute recovery (table 1). The results of Wilcoxon Test (p<0.05) showed that EG had an effect on anaerobic 0.017<0.05 with an increase in time of 9.11 seconds. CG also had an effect on anaerobic 0.042<0.05 with an increase in time of 4.82 seconds. However, there was a difference in groups using the Mann-Whitney test 0.010<0.05. These findings reinforce the benefits of interval training in increasing anaerobic energy expenditure. This study suggests the integration of interval training into boxing training to improve recovery, strength, and endurance. Given the limited sample size, training program, and previous training conditions of the athletes, future studies are needed for further verification.